Role of diagnostic laparoscopy in the management of female infertility - Katke, Rajshree Dayanand; Kiran, Usha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: With recent improvements in the assisted reproductive technology (ART), there has been a growing tendency that bypasses diagnostic laparoscopy and proceeds directly to ART. Therefore, the value of diagnostic laparoscopy in current fertility practice is under debate. The objective of this study was to study role of diagnostic laparoscopy in the management of unexplained infertility. Methods: 50 case of primary or secondary infertility with unknown etiology that underwent diagnostic laparoscopy in a tertiary care institute. Diagnostic laparoscopy was offered as a final option for patients with normal diagnostic workup for infertility like semen analysis, ovulation testing, ultrasound examination, hysterosalpingogram, and testing for ovarian reserve. Outcomes in terms of cause detected and immediate laparoscopic management done which is helpful in improving fertility. Results: Out of 50 cases studied, in 27 cases we found most probable cause of infertility and in remaining 23 cases we did not found any cause of infertility. Of the 27 cases, 11 cases had endometriosis, 5 cases had multiple pelvic adhesions, 5 cases of bulky cystic ovaries, 3 cases had combined endometriosis with pelvic adhesions and 2 cases had bilateral tubal blockade contrary to hysterosalpingographic findings, 1 case showed combination of cystic ovaries with pelvic adhesions. Intraoperative adhesiolysis, endometriosis ablation, and ovarian drilling were done in respective cases. Conclusions: We concluded that Laparoscopy has important role in the diagnosis and treatment of unexplained infertility. It also helps in Prediction and improvement of success rate of assisted reproductive technologies like IUI and IVF.